Pengembangan Video Pembelajaran Materi Pendistribusian Kembali Pendapatan Nasional Kelas VIII di MTsN 2 Nganjuk - Septia Ni’matul Lailiyah; Hendra Pratama (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2025)
This study is motivated by the challenges students face in understanding the material on national income redistribution in the eighth-grade social studies curriculum, primarily due to its abstract presentation and lack of visual aids. Teachers also struggle to create innovative teaching media, and the available textbooks do not provide sufficient illustrative support. To address these issues, this research develops a video learning medium aimed at outlining the development steps, assessing the validity of the produced media, and evaluating its effectiveness in enhancing student comprehension at MTsN 2 Nganjuk. Educational media play a crucial role in facilitating and clarifying understanding of the material. One continually evolving form of media is educational videos, which can convey concepts and procedures concretely while boosting student motivation and retention. The research questions are: (1) What are the steps in developing video learning media for the national income redistribution material for eighth grade at MTsN 2 Nganjuk? (2) What is the validity level of the developed video learning media for this material? (3) How effective is the developed video learning media in improving student understanding? The study aims to determine the development steps, validity, and effectiveness of the video learning media. Utilizing the Research and Development (R&D) model with ten steps from Borg and Gall, the study assesses the validity of the video learning tool. The subjects include 30 students from class VIII 1 at MTsN 2 Nganjuk. Validity tests yielded percentages of 92% from content experts, 89% from media experts, 82% from language experts, and 98% from the social studies teacher. Effectiveness testing using the Paired Sample T-Test showed a significance level of 0.001, indicating a significant improvement in student learning outcomes after using the video. Thus, the video on national income redistribution is validated by experts and proves effective in enhancing student learning outcomes.